2020
DOI: 10.5812/ijp.97311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Success Rate of Pulp Treated Primary Molars Restored with Stainless Steel Crown (SSC) Versus Glass Ionomer-SSC: A Double-Blind Randomized Clinical Trial

Abstract: Background:Maintaining an adequate coronal sealing is of a great importance and is the necessary prerequisite to maximize the long-term success rate of pulpotomy. Objectives: To compare the clinical and radiographic success of pulpotomized primary molars restored with stainless steel crown (SSC) versus glass ionomer (GI)-SSC. Methods: In this clinical trial, 47 children with age range of 4 -8 years, requiring pulpotomy for both primary mandibular second molars were recruited. Teeth were randomly treated either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Despite the fact that SSC has been the recommended treatment for many years, some researchers have stated that there is no strong evidence that SSC is preferable to alternative restorations and that the type of restoration has no impact on the success of vital pulp therapy. [52][53][54] Dimitraki et al (2019) 22 , and Choe et al (2017) 55 reported that class I cavities had showed greater success rates than class II cavities in primary teeth treated by DPC. Also, Franzon et al (2014) 28 stated that teeth with occlusal cavities treated by IPC showed higher success rate than teeth with proximal cavities treated by IPC.…”
Section: Celiberti Et Al (2006)mentioning
confidence: 99%
“…Despite the fact that SSC has been the recommended treatment for many years, some researchers have stated that there is no strong evidence that SSC is preferable to alternative restorations and that the type of restoration has no impact on the success of vital pulp therapy. [52][53][54] Dimitraki et al (2019) 22 , and Choe et al (2017) 55 reported that class I cavities had showed greater success rates than class II cavities in primary teeth treated by DPC. Also, Franzon et al (2014) 28 stated that teeth with occlusal cavities treated by IPC showed higher success rate than teeth with proximal cavities treated by IPC.…”
Section: Celiberti Et Al (2006)mentioning
confidence: 99%